Dynamics of high-current ion beam in the drift gap of induction accelerator at different variants of charge compensation - Karas, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2014)
In this paper the dynamics of the high-current ion beam (HIB), compensated by the electron beam by current density and partly by charge, in the drift gap (DG) of the linear induction accelerator with the collective focusing is studied. We have considered the HIB space charge compensation by thermal electrons, which are held in the DG by a magnetic field, which has mirror configuration. The dynamics of the beams at different variants of HIB space charge compensation has been studied. Found that in the presence of a programmed injection of additional electrons from the right side, the divergence of the HIB is practically absent, and its current at the exit of the DG differs slightly from the initial.